2011
DOI: 10.1088/1674-1056/20/3/030201
|View full text |Cite
|
Sign up to set email alerts
|

Conformal invariance and a kind of Hojman conserved quantity of the Nambu system

Abstract: Conformal invariance and a kind of Hojman conserved quantity of the Nambu system under infinitesimal transformations are studied. The definition and the determining equation of conformal invariance of the system are presented. The necessary and sufficient condition under which the conformal invariance of the system would have Lie symmetry under infinitesimal transformations is derived. Then, the condition of existence and a kind of Hojman conserved quantity are obtained. Finally, an example is given to illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…4 of the symmetry algebra and subject it to various adjoint transformations to simplify it as much as possible. [29] The adjoint action is given by the Lie series (20) where…”
Section: Symmetry Reduction Methods and Optimal Systemmentioning
confidence: 99%
“…4 of the symmetry algebra and subject it to various adjoint transformations to simplify it as much as possible. [29] The adjoint action is given by the Lie series (20) where…”
Section: Symmetry Reduction Methods and Optimal Systemmentioning
confidence: 99%
“…[50]. When α → 1, using conditions (33), the fractional Nambu equations (29) can be reduced to integer-order generalized Hamiltonian equations:…”
Section: The Relation Between a Fractional Nambu System And A Fractiomentioning
confidence: 99%
“…Ditto et al [21,22] presented the quantization problem of Nambu mechanics and indicated the validity of the fundamental identity of Nambu mechanics also at the quantum level. With the further developments in of science and technology, the Nambu dynamical system has played an important role not only in modern mechanics, but also in physics, engineering science, nonlinear science, celestial mechanics and so on [23][24][25][26][27][28][29][30][31][32][33]. However, no work had so far been published on the dynamics of Nambu systems with fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…The key question to the conformal invariance of dynamics is to find out the conformal factor. Considerable progress has been made over past years in the application of conformal invariance to mechanical systems [20][21][22][23][24][25]45]. However, the application of conformal invariance to thin elastic rod has never been investigated.…”
Section: Introductionmentioning
confidence: 99%